Wave propagation in stratified medium: new matrix form of the wave difference equation - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2018)
Results of research of possibility of transformation of a wave difference equation into a system of the first-order difference equations are presented. In contrast to the method used previously, an unknown grid function is split into two new auxiliary functions, which have definite properties. Several examples show that proposed approach can be used for solving different physical problems associated with the wave propagation in one dimension.